Estimated Costs and Returns of Hemp Flower Production - Trent Blare; Zachary Brym; Andres Bejarano Loor; Fredy H. Ballen (EDIS, 2024)
The purpose of this document is to provide a framework and provisional values to estimate costs and returns of hemp flower production for commercial producers in Florida. Written by Trent Blare, Zachary Brym, Andres Bejarano Loor, and Fredy H. Ballen, and published by the UF/IFAS Department of Agronomy, August 2024.